Estrategias didácticas aplicadas en la asignatura de Historia en el BGU de la Unidad Educativa Cicalpa, cantón Colta - Barragán Erazo, Jackeline Paola (2024)
This research aimed to determine the teaching strategies applied to the History subject in the Baccalaureate of the Unidad Educativa Cicalpa, Colta Town. A mixed-type approach was used; the qualitative approach allowed for generating concepts about teaching strategies, while the quantitative approach helped to identify them. The research design was descriptive; for this, there was a population of 60 students who belonged to the three years of baccalaureate. A survey of 11 questions was carried out: 1 multiple choices, 10 dichotomous, and an 8-question interview with History teachers. The results demonstrated that the pedagogical strategies are widely adopted in all the courses studied. These include problem-based learning, case studies, collaborative learning, project-based learning, the creation of teaching materials, and discussions or gatherings. There is also a minority use of other techniques, such as simulations, educational games, technology-based learning, and visits to museums or historical places. The rural context and the technological limitations of the institution influence the selection and application of these strategies, adapting them to maximize effective learning of history